Relationship Between Histopathology Grading (Nottingham System) and Expression of HER2/Subtype Luminal B in Breast Carcinoma with Lymph Node Metastases - Irmaya, Dita; Hernowo, Bethy S.; Dewayani, Birgitta M. (Majalah Patologi Indonesia, 2025)
Background Molecular subtypes of breast carcinoma, histological grade, and lymph node msetastases are significant in determining the therapy and prognosis of the patient. The luminal B subtype comprises 15%-20% of breast cancers and has a more aggressive phenotype, higher histological grade, proliferative index, and a worse prognosis. This study aimed to evaluate the relationship between histopathological grading and expression of  HER2 with lymph node metastases in luminal B subtype breast carcinoma. Methods We analyzed 279 invasive breast carcinoma luminal-B subtypes from the anatomic pathology laboratory of Dr. Hasan Sadikin Bandung between January 2017 and March 2023. Histological grade using the Nottingham system, expression of HER2 using immunohistochemistry examination, and lymph node metastases status were obtained from anatomic pathology records. The association between histological grade and expression of HER2 with lymph node metastases was examined with chi-square tests. Result: In the current study, we included 279 subjects, dominated by patients whose age at diagnosis was less than 50 years old. The Chi-square analysis showed no statistically significant difference in tumor size between patients with metastasis and those without metastasis,P = 0.74. The Chi-square analysis showed a significant relationship between histopathological grade and lymph node metastases, p < 0.01 and expression HER2 status and lymph node metastasis  p < 0.05 Conclusion This study found that patients present with larger tumors classified as T3 and moderate to poor grade III and grade II histological grades. The statistical analysis showed no significant difference in the age of diagnosis between patients with metastasis and those without. However, the Chi-square analysis revealed a significant correlation between the histopathological grade and HER2 expression with lymph node metastasis.